Computational Modeling for Industrial-Organizational Psychologists (Taylor & Francis, 2024)
Computational Modeling for Industrial-Organizational Psychologists; Jeffrey B. Vancouver; Mo Wang; Justin Weinhardt; Jeffrey Vancouver; SIOP Organizational Frontiers Series; SIOP; Society for Industrial and Organizational Psychology; SIOP Organizational Frontiers; computational modeling; computerational models; I/O psychology; vocational psychology; work psychology; organizational psychology; human resource management; organizational behavior; organizational science
English
Keywords: Philosophy: aesthetics; The arts: general issues; Computational Modeling for Industrial-Organizational Psychologists; Jeffrey B. Vancouver; Mo Wang; Justin Weinhardt; Jeffrey Vancouver; SIOP Organizational Frontiers Series; SIOP; Society for Industrial and Organizational Psychology; SIOP Organizational Frontiers; computational modeling; computerational models; I/O psychology; vocational psychology; work psychology; organizational psychology; human resource management; organizational behavior; organizational science